Bangladesh Perspective: Vehicle Speed Proposition System using Localized Wireless Identification - Md. Mamunoor Islam; Mehdi Hasan Chowdhury (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Even in the era of advanced engineering, road accident has been a regular phenomenon causing death of many people in Bangladesh due to over speeding action of reckless drivers. There are several key places (such as schools, colleges, hospitals, highways and constructional areas etc.) where the speed of the vehicle should be lessened to avoid accidents. The roads and highways authority may place the speed limiter signboards in these areas to avoid these accidents, but these are frequently overlooked by the drivers. So this paper demonstrates a wireless forewarning system which will aid to control the speed of the vehicles at speed restricted areas. The whole system is established on the basis of radio frequency (RF) communication. There are two parts of this system named as transmitting unit and receiving unit. Each RF transmitter positioned on the roadside will be transmitting the code signal continuously. Whenever the vehicle enters the range of transmission, the RF receiver which is attached in the vehicle, will receive the signal and will display the information in a LCD monitor by notifying the driver to reduce the speed while going through that area.